Key technologies of SDN in transport network and application scenarios of traffic engineering - HANGQi Z (Dianxin kexue)
With the development of SDN technology,the outlook of its application is getting bright.The basic features of SDN and key technologies in transport network were first analyzed and concluded.Secondly,with the association of simulation plane,typical traffic engineering application scenarios were introduced.At last,the conclusion of scenarios application and the value of SDN usage were also extracted and abstracted in order to propose necessary suggestion for future deployment.